Tantangan Intelijen dalam Kontra-Terorisme di Indonesia: Suatu Pandangan - Emil Mahyudin (Intermestic: Journal of International Studies, 2016)
The September 11th 2001 attact in the United States has become the world’s turning point, from how terrorism actors operate globally through networks to how states and international relations actors response towards it. This article about the challenges for intellegence in counter-terrorism in Indonesia and the preventive actions needed especially in the use of information technollogy, as the form of detection effort and early warning for the terrors. Through the literature reviews, it is found that in practice the Indonesians intellegence activities are tend to not well organized from one institution to another because of the trust-deficit, overlapping activities and accuration of intellegence, and the lack of concrete actions in eliminating the terrorism threats in cyber sphere. It can be concluded that the comprehensive and integrative efforts are needed in organizing the intelligence in Indonesia. On the other hand, the national strategy on counter-terrorism in cyber area through the comprehensive use of information technology on the cyber terrorism threats.